Student’s Response Toward Utilizing Discord Application as an Online Learning Media in Learning Speaking at Senior High School - Aulia Ramadhan (Jurusan Sastra Indonesia, 2021)
Technology and education are different things, but in this modern era we all can see that these two things are inseparable and become necessities. This present study is aimed to know the students’ response toward utilizing Discord application as an online learning media in learning speaking at Senior High School. Therefore, This study investigates the effectiveness of the Discord application as an online learning medium, and also investigates the students' motivation to learn speaking skills while learning using the Discord application. This study uses a qualitative approach and uses an interpretative studies research design. Participants in this study involved 6 students' in 12th grade in Senior High School SMA Negeri 1 Cikarang Timur. Online observations, online interviews, and virtual documentation are used to obtain data as information or answers related to the research question. This research found that , the utilizing of the Discord application as an online learning media in speaking learning has several benefits and advantages. The discord application facilitates the convenience of students in the learning experience such as a very effective, practical, lighter application used in various smart phones because of its small size, has a Voice channel feature that allows interaction via voice in the discord room.Keywords : Discord Application, Student’s Response, Speaking.